Assessment of water quality in parts of industrial area of Nnewi north local government area, southeast, Nigeria - A. Agbonma, Ifeanyichukwu; Okeyeh, Elizabeth; Emeh, Chukwuebuka (International Journal of Advanced Geosciences, 2020)
Industrial pollution in Nnewi-North local Government Area, Anambra state, South Eastern Nigeria has become a major environmental concern due to unregulated discharge of industrial emissions and effluents into the environment. However, the paucity of environmental data and research from this area makes it difficult to ascertain the effect of the industrial activities on the surrounding environment. For this reason, it became imperative to assess the impact of the industrial activities on the quality of the surrounding surface and groundwater for agricultural and domestic purposes. To this end, an integration of geological, and geochemical method of analyses was adopted. The geology of the study area was determined through surface geological mapping, 22 groundwater water samples, and 3 surface water samples were collected within the study area following American Public Health Association (APHA) procedures. The sample collections were done in such a way that consider lateral and during the dry season. Atomic Absorption Spectroscopy (AAS), titrimetric and gravimetric, analytical method was used to ascertain the chemical composition of the water. The laboratory and field results were analyzed by employing several geochemical indices calculations, and inferential and summary statistics. Results from groundwater indices such as GWQI, HPI, HEI and Cd calculated with respect to WHO, 2011 and NSDWQ for both dry seasons revealed that the groundwater was contaminated, and unfit for drinking. Then from the surface water samples result of irrigation quality indices such as TH, MH, SAR, RSBC, Na% and PI calculated for dry season, indicated that the surface water is fit for irrigation for all irrigation indices expect RSBC and MH. From the statistics of PCA and T-test it was statistical proven that the source of contamination of surface and groundwater was anthropogenic (that is from industrial waste) and geogenic. Since the groundwater is contaminated, it is therefore recommended that the water should be treated before consumption.Â